Evidencing an inner-sphere mechanism for NHC-Au(I)-catalyzed carbene-transfer reactions from ethyl diazoacetate - Fructos, Manuel R.; Urbano, Juan; Díaz-Requejo, M. Mar; Pérez, Pedro J. (Beilstein Journal of Organic Chemistry, 2015)
Kinetic experiments based on the measurement of nitrogen evolution in the reaction of ethyl diazoacetate (N2CHCO2Et, EDA) and styrene or methanol catalyzed by the [IPrAu]+ core (IPr = 1,3-bis(diisopropylphenyl)imidazole-2-ylidene) have provided evidence that the transfer of the carbene group CHCO2Et to the substrate (styrene or methanol) takes place in the coordination sphere of Au(I) by means of an inner-sphere mechanism, in contrast to the generally accepted proposal of outer-sphere mechanisms for Au(I)-catalyzed reactions.
Keywords: carbene transfer; inner sphere; gold catalysis; O–H functionalization; olefin cyclopropanation